2015
DOI: 10.1021/co500146u
|View full text |Cite
|
Sign up to set email alerts
|

Diversity-Oriented Approaches to Polycyclics and Bioinspired Molecules via the Diels–Alder Strategy: Green Chemistry, Synthetic Economy, and Beyond

Abstract: We describe diverse approaches to various dienes and their utilization in the Diels-Alder reaction to produce a variety of polycycles. The dienes covered here are prepared by simple alkylation reaction or via the Claisen rearrangement or by enyne metathesis of alkyne or enyne building blocks. Here, we have also included the Diels-Alder chemistry of dendralenes, a higher analog of cross-conjugated dienes. The present article is inclusive of o-xylylene derivatives that are generated in situ starting with benzosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 278 publications
0
30
0
Order By: Relevance
“…Currently, some reports demonstrated that tetrazines can react rapidly and specically with strained alkenes to form stable adducts in inverse electron demand Diels-Alder (IED-DA) cycloaddition reactions. [5][6][7] This chemistry is orders of magnitude faster than the classical cycloadditions and has been used in live cell labeling. 8,9 Very recently, with the development of IED-DA cycloaddition reaction in bioorthogonal eld, the method for specic labeling of proteins in complex biological systems is the currently attractive area.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, some reports demonstrated that tetrazines can react rapidly and specically with strained alkenes to form stable adducts in inverse electron demand Diels-Alder (IED-DA) cycloaddition reactions. [5][6][7] This chemistry is orders of magnitude faster than the classical cycloadditions and has been used in live cell labeling. 8,9 Very recently, with the development of IED-DA cycloaddition reaction in bioorthogonal eld, the method for specic labeling of proteins in complex biological systems is the currently attractive area.…”
Section: Introductionmentioning
confidence: 99%
“…[10] To generate new strategies in metathesis area and more specifically in ring-rearrangement metathesis (RRM) sequence, our group has explored the design and synthesis of several cyclic sulfones and related compounds. [11][12][13][14][15][16][17] Inspired by our earlier results, here we report a concise route for the rapid construction of fused tricyclic sulfone via RRM strategy. Our strategy aimed at assembling fused sulfones with varying ring size and for this purpose we begin with the synthesis of tricyclic sulfone with 6/7/6 fused ring system by employing RRM approach.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, with visible light radiation, the catalyst [Ru(bpz) 3 ] 2+ should be excited to be [Ru(bpz) 3 ] 2+ * to transfer electrons from the reactants in quenching. This is consistent with the experiment that [Ru(bpz) 3 ] 2+ * plays an important role in transferring the Ru + / Ru + * (t 2g ) 6 (e g ) 1 / (t 2g ) 5 (e g ) 2 44.90 4d 6 Ru 2+ / Ru 2+ * (t 2g ) 6 (e g ) 0 / (t 2g ) 5 (e g ) 1 49.48 (t 2g ) 6 (e g ) 0 / (t 2g ) 4 (e g ) 2 106.84 4d 5 Ru 3+ / Ru 3+ * (t 2g ) 5 (e g ) 0 / (t 2g ) 4 (e g ) 1 57.00 (t 2g ) 5 (e g ) 0 / (t 2g ) 3 (e g ) 2 114.14 a *Means the excited states of the atom.…”
Section: The Charge Transfer By Ruthenium Photosensitizermentioning
confidence: 99%
“…The Diels-Alder (D-A) reaction [1][2][3][4] is an effective method to synthesis six-membered rings with high selectivity, 5 where the dominant interaction is the donation of electron density from the HOMO of diene to the LUMO of dienophile. 6,7 Therefore, it is common to apply [4 + 2] cycloaddition in the drug synthesis, such as those of the chalconoid natural products and the pre-nylavonoid D-A natural products.…”
Section: Introductionmentioning
confidence: 99%